Enhancing digital citizenship education in Saudi Arabian elementary schools: designing effective activities for curriculum integration - Alenezi, Naji; Alfaleh, Maha (Frontiers in Education, 2024)
In an era where digital technologies significantly influence children’s lives globally, promoting responsible digital citizenship is crucial to equip them with the skills to navigate the digital world safely and responsibly. This study examines the integration and current state of Digital Citizenship Education (DCE) in Saudi Arabian elementary schools, assessing its alignment with international standards and identifying local challenges faced by educators, and pedagogical strategies used. Employing a mixed-methods approach, quantitative data was collected through surveys from 398 teachers and qualitative insight gained from semi-structured interviews with 15 teachers. Quantitative analysis employed descriptive statistics and multivariate analysis of variance (MANOVA) to explore demographic influences on DCE practices. The findings reveal a strong emphasis on Digital Emotional Intelligence and Digital Security, Privacy, and Health and Wellness; however, significant gaps exist in Digital Participation and Agency, and Digital Footprint and Identity. These gaps are attributed to factors such as insufficient teacher training, lack of effective structured guidelines, and insufficient resources. Significant interaction effects between teachers’ demographics and DCE perceptions highlight the need for targeted professional development. The study concludes with actionable recommendations for enhancing curriculum integration, teacher training, and policy development to promote digital citizenship among elementary school students aligned with global standards.